Academic Library Roles in Preventing Plagiarism - Anton Risparyanto; Irawati Irawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
This collaborative research illustrates the role of UII Yogyakarta Library and UIN Alauddin Makassar Library in preventing plagiarism. The data at UII Yogyakarta were obtained by interviewing 25 students who were compiling their final scientific papers, also through observation and focused discussion. At UIN Alauddin Makassar, the data were obtained by interviewing 8 Turnitin instructors and administrators, also through observation and documentation. The research data were analyzed using quantitative-qualitative descriptive methods. The results showed that the Library of UII Yogyakarta and UIN Alauddin Makassar had an important role in encouraging students to be aware of plagiarism through awareness-raising, honesty fostering, and tutorials on understanding plagiarism itself. This study also found that the students were more proactive with the issue of plagiarism by discussing together and socializing the rules related to plagiarism in these two institutions.